MicroRNA-339 inhibits human hepatocellular carcinoma proliferation and invasion via targeting ZNF689 - Zeng H; Zheng J; Wen S; Luo J; Shao G; Zhang Y (Dove Medical Press, 2019)
Hui Zeng,1 Jiaping Zheng,1 Song Wen,1 Jun Luo,1 Guoliang Shao,1 Yongjun Zhang2 1Department of Interventional Radiology, Zhejiang Cancer Hospital, Hangzhou 310022, Zhejiang, P.R. China; 2Department of Integration of Traditional Chinese and Western Medicine, Zhejiang Cancer Hospital, Hangzhou 310022, Zhejiang, P.R. China Background: Hepatocellular carcinoma (HCC) is the second leading cause of cancer mortality worldwide, however, the prognosis for HCC remains unsatisfactory. This study aimed to explore the role of miR-339-5p in HCC.Methods: We first used quantitative real-time PCR to examine the level of miR-339-5p in HCC tissues. Then we further adopted Western blotting assay, CCK8, cell invasion assays, apoptosis detection assay, and luciferase assay to analyze how it mediate the development of HCC.Results: We found that miR-339 is significantly decreased in primary HCC tissues. Overexpression of miR-339 in HCC cells remarkably suppressed proliferation and invasion and induced apoptosis. However, silencing miR-339 in HCC cells promoted proliferation and invasion, and reduced apoptosis. Moreover, we demonstrated that ZNF689 is a target of miR-339 and there is a negative correlation between miR-339 and ZNF689 expression in the HCC tissues. Overexpression of ZNF689 in miR-339-overexpressing HCC cells partially antagonized the inhibitory effects of miR-339. Conclusion: Our study revealed that miR-339 inhibits HCC growth through targeting oncoprotein ZNF689 and restoration of miR-339 might be feasible therapeutic strategy for HCC treatment. Keywords: miR-339-5p, HCC, ZNF689, treatment, proliferation